Bee venom ameliorates gentamicin-induced kidney injury by restoring renal aquaporins and enhancing antioxidant and anti-inflammatory activities in rats - Abdelrahaman, Doaa; Shanab, Obeid; Abdeen, Ahmed; Abdelkader, Afaf; Elazab, Khalid M.; Kouriem, Hagar; Maher, Zainab M.; Abu-Almakarem, Amal S.; Mohamed, Mohamed E.; Elbastawisy, Yasser M.; Elsehrawy, Mohamed G.; Badawy, Abdelnaser A.; et al. (Frontiers in Pharmacology, 2025)
Introduction:Gentamicin (GM) is a frequently used aminoglycoside for managing serious illnesses; nonetheless, renal complications limit its use. Bee venom (BV) is a biological toxin that exhibits anti-inflammatory and antioxidant activities. This study was designed to explore the mitigating effect of BV remediation on GM induced renal injury.Methods:Twenty male rats were divided into four groups (five rats each), namely, control (saline subcutaneously); BV group (1 mg/kg S/C twice weekly for 1 month); GM group (100 mg/kg i. p. for 1 week); and GM-BV group (the same aforementioned dosages of GM and BV, with GM administered in the last week for 4 weeks).Results and discussion:BV mitigated the GM-inflicted kidney damage, as evidenced by a substantial improvement in the renal function and oxidative state. In addition, a downregulation in the expression of inflammatory biomarkers (Casp-1, IL-6, TNF-α, and NF-κB/P65/P50) and an upregulation of oxidative stress marker expression (NRF2) were noticed. BV upregulated the expression of aquaporins (AQPs) and renal water channel proteins (AQP1 and AQP2), which are useful for the early detection of renal injury. Additionally, BV exposure exerted a mitigating effect on the apoptotic cascade, as evidenced by the downregulation of cleaved Caspase-3 (Casp-3) and cytochrome c (Cyto c). BV administration also led to an improvement in RBC, WBC, and platelet counts, along with enhanced Hb levels. Interestingly, BV could protect against GM triggered nephrotoxicity.